A preliminary study of cross-amplified microsatellite loci using molted feathers from a near-threatened Painted Stork (Mycteria leucocephala) population of north India as a DNA source - Bharat Bhushan Sharma; Basu Dev Banerjee; Abdul Jamil Urfi (BMC Research Notes, 2017)
Abstract Objective In continuation of an earlier study in which we reported the cross-amplification of Wood stork microsatellites on the DNA obtained from molted feathers of Painted stork (Mycteria leucocephala), here we investigated the nature of cross-amplified microsatellites and the effect of non-invasive samples on cross-amplification success. In a limited manner, we also addressed the genetic diversity and differentiation in a north Indian population of the Painted Stork examined over three nesting seasons. Results Among the nine cross-amplified loci, only 5 were polymorphic. Three and 6 loci exhibited low (< 50%) and high amplification success rates (> 80), respectively. For 36 of 145 samples most of the loci failed to amplify. For genetic diversity, only 3 loci could be used since others exhibited low amplification and linkage disequilibrium. Probability of identity (0.034) was not low enough to develop a confidence that the similar genotypes originate from the same individual. Forty-two unique genotypes were identified. In 3 loci, a low to moderate level of genetic diversity (mean He = 0.435) was reported. Non-significant Fst (0.003, P = 0.230), G’stH (0.005, P = 0.247) and Dest (0.003, P = 0.250) values indicate a lack of structuring in temporally distributed populations of Delhi Zoo. The limitations and uniqueness of this study are discussed.